Efektywność międzynarodowych reżimów nieproliferacji broni biologicznej i chemicznej - Stempień, Marta; Tołwiński, Maciej (Polityka i Społeczeństwo, 2021)
International non-proliferation regimes will only be effective when the efforts of the signatories of international agreements, regional or bilateral will be increased, because declarative expression of support for the various forms of initiatives of the international community often end up at this level, as shown by the cases of chemical weapons use in the Syrian Civil War. The main aim of this article is to show the management problems of global non-proliferation regimes of biological and chemical weapons. The authors made a comparative analysis of two non-proliferation regimes. This combination helped to achieve the second objective of the article, which is to identify the major challenges and threats generated by these regimes, which allowed the formulation of the conclusion that in order to strengthen them, the international community must take comprehensive action, including reducing the threat of terrorist organizations.